Legal Protection In Indonesia Against Badal Hajj Fraud - Fauziah Nuraini, Dewi; Maulida, Nor; Fauzi, Nazela (Penerbit Hellow Pustaka, 2024)
This study aims to find out more deeply about badal haji in order to avoid badal haji fraud and legal steps that can be taken when fraud has occurred in the implementation of badal haji. Using normative legal research methods. Data collection is done by literature study which is researched by conducting a review of legislation and literature on the subject under study. Prudence is one of the things that needs to be prioritized, in order to be careful in determining something, in this case related to badal haji, so as not to be deceived by unscrupulous people who seek profit in narrowness. By knowing the conditions, pillars and obligations of Hajj as well as the law and mechanism of badal haji, is also one way to avoid fraud. As for the case of fraud that has befallen a person who in this case is a participant in badal haji, whether there is a default or an act against the law and so on, legal protection in Indonesia can be a solution because then a person can know what steps to take in this case, such as; reporting to the police or by filing a civil lawsuit.